The central margins: Congo's transborder economy and state-making in the borderlands - Timothy Raeymaekers (Danish Institute for International Studies (DIIS), 2009)
This paper explores the connections between cross border trade, armed rebellion, and state making in the borderland of North Kivu province (eastern Democratic Republic of Congo) and Kasese (Western Uganda) during the recent war to peace transition (1990's-2003). Rather than collapsed statehood and economic development-in-reverse, the author argues that the interdependencies and accumulation strategies developed during Congo's protracted crisis have gradually made this borderland a crucial pillar in the equilibrium forces between formal and informal, state and non state actors and regulations in this territorial periphery - which has subsequently become a central margin in today's regional processes of state formation.
Keywords: 330; Regionaler Außenhandel; Krieg; Staatsgründung; Grenzgebiet; Kongo (Demokratische Republik); Uganda